Molecular diagnosis of visceral leishmaniasis in children of Basrah governorate, Iraq - Maha K. AL-Mishry (University of Thi-Qar Journal of Science, 2019)
The laboratory diagnosis of visceral leishmaniasis is based on microscopic examination, culture, serological tests and molecular methods. This study include 50 cases of suspected Visceral Leishmaniasis (VL) patients in 3 hospitals (Al-Basrah Maternity and Children, Al-Basrah General and Al-Tahreer) during the period from December 2011 to July 2012, and 25 healthy child from health care centers in Basrah. We examined their Bone Marrow aspirates by microscopic examination and DNA amplification from peripheral blood by Polymer Chain Reaction (PCR) technique .We calculated positive- negative predictive values and the sensitivity-specificity of these diagnosis tests. Positive predictive value of microscopic examination were 45 (90%) and (10%) negative for visceral leishmaniasis and for PCR 42(84%) positive , 8 (16%) negative ,the sensitivity and specificity for PCR 93.3% and 100% respectively ,with statistically significant different (p<0.01).